2020
DOI: 10.3390/su12072959
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometrics Review on Land Ecosystem Service Research

Abstract: Humans can derive the benefits from the ecosystem to satisfy human needs as well-being. Therefore, good ecosystem management is the intermediary between ecosystems and human well-being. The ecosystem services depend on the supply of nature, and also reflect the value orientation of human beings, as the basis for the realization of human survival and cultural development. Land ecosystem services are the core and hot topic of ecological research. Under the current severe depletion of land use, this research eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 60 publications
(52 reference statements)
0
18
0
1
Order By: Relevance
“…To accurately and comprehensively analyze the development status and research hotspots in the field of food security and to develop visualizations thereof, this paper analyzes the research status and hotspot trends in the field of food security using the software packages CiteSpace 5.5, VOSviewer, and Bibliometrix. The detailed steps for this research are shown in Figure 1. matrix; the co-citation, coupling, co-, and co-word analyses; and other aspects of research and visualization [52] from recent years in various fields of scientific research [53][54][55]. VOSviewer, developed by Nies Jan van Eck and Ludo Waltman, is widely used in all kinds of co-occurrence analysis software, especially in terms of keyword co-occurrence analysis [56][57][58][59][60][61].…”
Section: Methodsmentioning
confidence: 99%
“…To accurately and comprehensively analyze the development status and research hotspots in the field of food security and to develop visualizations thereof, this paper analyzes the research status and hotspot trends in the field of food security using the software packages CiteSpace 5.5, VOSviewer, and Bibliometrix. The detailed steps for this research are shown in Figure 1. matrix; the co-citation, coupling, co-, and co-word analyses; and other aspects of research and visualization [52] from recent years in various fields of scientific research [53][54][55]. VOSviewer, developed by Nies Jan van Eck and Ludo Waltman, is widely used in all kinds of co-occurrence analysis software, especially in terms of keyword co-occurrence analysis [56][57][58][59][60][61].…”
Section: Methodsmentioning
confidence: 99%
“…As pointed above, bibliometric studies are valuable, yet, while documenting what is out there is interesting, the analysis needs to dive into the substance of the works in order to advance the understanding of the phenomenon under investigation. Therefore, when designing this study special attention was put on the works published by the developers of Bibliometrix [24,25] as well as on other relevant works that employ this software package and go beyond descriptive findings to create interpretations (e.g., [26][27][28]).…”
Section: Data Treatmentmentioning
confidence: 99%
“…The overview highlights the diverse facets of land ecosystem services and the practical application of land ecosystem services. Xie et al, 2020 Virtualization, soil, water, crops, plants…”
Section: Land Ecosystemmentioning
confidence: 99%